The Effectiveness of Non-Litigation Mechanisms in Resolving Consumer Disputes in South Tangerang City - Dena Vera Silvana (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
The increasing volume of goods and services transactions in South Tangerang City, in line with the growth of the trade and service sectors, has led to a higher potential for consumer disputes. These disputes generally relate to product non-conformity, services that disadvantage consumers, and the suboptimal fulfillment of consumer rights. Dispute resolution through litigation is often considered less effective due to the time, cost, and complex procedures involved. Therefore, non-litigation consumer dispute resolution mechanisms have become an important alternative in ensuring the protection of consumer rights in a manner that is fast, simple, and equitable. However, the implementation of non-litigation mechanisms in South Tangerang City still faces various challenges, including institutional limitations, low levels of public legal literacy, and issues related to practical effectiveness. This study aims to: (1) analyze the implementation of non-litigation consumer dispute resolution mechanisms in protecting consumer rights; (2) identify the obstacles encountered in their implementation; and (3) formulate strategies to strengthen these mechanisms to enhance their effectiveness. This research employs an empirical juridical approach with a descriptive-analytical design. Data were collected through literature review and field research, including interviews and observations involving relevant stakeholders and consumers who have experienced disputes. The data were analyzed qualitatively to provide a comprehensive understanding of the implementation of non-litigation dispute resolution mechanisms. The findings indicate that non-litigation mechanisms have not yet operated optimally due to limited public awareness, institutional constraints, and insufficient dissemination of information. Nevertheless, these mechanisms hold significant potential to improve access to justice if strengthened through enhanced legal literacy, institutional capacity, and more effective implementation at the local level.